PEGylated poly(ester amide) elastomer scaffolds for soft tissue engineering. (10th January 2017) - Xue, Yingfei; Yatsenko, Tatyana; Patel, Akhil; Stolz, Donna Beer; Phillippi, Julie A.; Sant, Vinayak; Sant, Shilpa
Abstract : Biodegradable synthetic elastomers with tunable mechanical and physicochemical properties remain attractive materials for soft tissue engineering. We have recently synthesized novel poly(1, 3‐diamino‐2‐hydroxypropane‐ co ‐glycerol sebacate)‐ co ‐poly(ethylene glycol) (APS‐ co ‐PEG) biodegradable elastomers. This class of PEGylated elastomers has widely tunable mechanical and degradation properties compared wtih currently available biodegradable elastomers. To further investigate the biological application of this class of elastomers, we fabricated hybrid APS‐ co ‐PEG/polycaprolactone (PCL) porous scaffolds by electrospinning. The fiber morphology, chemical composition, mechanical properties, degradability, and cytocompatibility of hybrid APS ‐co ‐PEG/PCL electrospun scaffolds were characterized. These scaffolds exhibited a wide range of mechanical properties and similar cytocompatibility to PCL scaffolds. Importantly, PEGylation inhibited platelet adhesion on all APS ‐co ‐PEG/PCL electrospun scaffolds when compared with PCL and APS/PCL scaffolds, suggesting a potential role in mitigating thrombogenicity in vivo . Additionally, APS‐ 25 PEG/PCL scaffolds were found to be mechanically analogous to human heart valve leaflet and supported attachment of human aortic valve cells. These results reveal that hybrid APS‐ co ‐PEG/PCL scaffolds may serve as promising constructs for soft tissue engineering, especially heart valve tissue engineering. Copyright © 2017 John Wiley & Sons, Ltd.